Extraction of honokiol from Artemisia argyi and in vitro and in vivo investigation of its antifungal activity. Issue 4 (16th February 2023) - Wang, Xianxian; Han, Xiaobin; Wang, Shu; Wang, Yaobin; Wang, Peng; Zhao, Zhongli; Qin, Huimin; Jing, Changliang; Liang, Chen
Abstract: Extracts from plants used in Chinese medicine can be good sources of fungicides for agricultural applications. In this study, we separated and identified antifungal compounds from four traditional Chinese medicine extracts and evaluated their antifungal activities in vitro and in vivo . In vitro, honokiol extracted from Artemisia argyi showed broad-spectrum antimicrobial and mycelial inhibitory activity with EC50 in the range 3.56 − 33.85 μg/mL against eight plant pathogens. q-PCR indicated that honokiol might induce cell cancerisation and inhibit cellular respiration, which provided significant insights into honokiol function in tobacco resistance to molecular mechanisms of the phytopathogenic fungus Phytophthora nicotianae . In vivo, honokiol significantly decreased the rate of fungal infection in eggplants, potatoes, grapes, cherry tomatoes, and cucumbers, and enhanced disease resistance in tobacco. Overall, our results indicate that honokiol has the potential to control a variety of fungal and oomycete diseases, and A. argyi could be a source of honokiol. Graphical Abstract: UF0001